Principles of macroeconomics - Beveridge, Thomas M. (Prentice Hall, 1996)
"This textbook is a concise introduction to macroeconomics. Each chapter links the basics of economic theory with policy formulation on one hand and corporate behaviour on the other. Using examples and data from India it gives an insight into macroeconomic theory and its implications for the economy. This book is aided by simple diagrams, boxes, cases, and examples from real-life situations.